2014
DOI: 10.1186/1471-2377-14-146
|View full text |Cite
|
Sign up to set email alerts
|

Novel loss-of-function PRRT2mutation causes paroxysmal kinesigenic dyskinesia in a Han Chinese family

Abstract: BackgroundMutations in proline-rich transmembrane protein 2 (PRRT2) are a cause of paroxysmal kinesigenic dyskinesia (PKD). In this study, we investigated the PRRT2 gene mutation in a Chinese Han family with PKD and study the pathogenesis of the mutation with PRRT2 gene.MethodsPeripheral venous blood was taken from the family members. Sanger sequencing was used for novel mutation sequencing. For the pathogenesis with the novel mutation was analyzed by bioinformatics, real-time PCR, subcellular localization and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…Consistent with this result, a recent in vitro study also showed a decrease in synapses in cultured hippocampal neurons when Prrt2 was knocked down [32]. Delayed neuronal migration and abnormal spine density are frequently associated with various cognitive, learning and memory deficits [28, 3436]. Our results indicated that these defects may contribute to the severe encephalopathy caused by the rare homozygous or biallelic PRRT2 mutations [10, 15, 16, 37].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Consistent with this result, a recent in vitro study also showed a decrease in synapses in cultured hippocampal neurons when Prrt2 was knocked down [32]. Delayed neuronal migration and abnormal spine density are frequently associated with various cognitive, learning and memory deficits [28, 3436]. Our results indicated that these defects may contribute to the severe encephalopathy caused by the rare homozygous or biallelic PRRT2 mutations [10, 15, 16, 37].…”
Section: Discussionsupporting
confidence: 90%
“…Reduced expression has been reported in cells expressing other PRRT2 mutations [19, 33, 34] and could be a common functional loss of PKD-related mutations. It remains unclear whether the decreased protein level in cells was caused by decreased production, protein instability, or both.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, c.649dupC (p.R217Pfs*8) is the most frequent variant, accounting for 78.5% of mutation carriers . Truncated variants leading to conspicuous reduced protein level have been reported in various in vitro studies . Besides the truncated variants, about 29 missense variants of PRRT2 are documented in PRRT2 ‐related disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Amino acids used in calpain-resistant substitution mutants are highlighted with yellow. C, Lysates of Neuro2A cells transfected with PRRT2wt-EGFP cDNA (lanes 1-3), PRRT2 LSRHP243_247FIDDD-EGFP cDNA (244-uncleaved mutant; lanes 4-6), PRRT2 HSPP201_204IDDD-EGFP cDNA (201-mut; lanes 7-9), PRRT2 LAGPG251_255FIDDD-EGFP cDNA (252-mut; lanes 10-12) or PRRT2 LQQLV219_223FIDDD-EGFP cDNA (220-mut; lanes 13-15) were treated with 4 mM CaCl 2 and 16.8 ng/µL native calpain-1 at 30°C for 0 hr (lanes 1, 4, 7, 10, 13, 16), 0.5 hr (lanes 2, 5, 8, 11, 14, 17), or 2 hr (lanes 3,6,9,12,15), and then immunoblotted with anti-GFP antibody. A black arrowhead and arrow indicate the full-length PRRT2-EGFP (lanes 1, 4, 7, 10, 13) and 12K-CTF-EGFP (lanes 2, 3, 8, 9, 11, 12), respectively.…”
Section: F I G U R Ementioning
confidence: 99%
“…4 PRRT2 is composed of 340 amino acids, including a large intracellular domain (aa 1-268) harboring a proline-rich motif (aa 131-216), followed by an intramembrane region (aa 269-289) and a transmembrane domain (aa 318-338) at the carboxy (C)-terminal region (see Figure 1C). 5 Many of the PRRT2 mutations found in PKD patients result in truncation of PRRT2 protein lacking transmembrane regions, causing a rapid degradation or subcellular mislocalization, 1,6,7 | 181 HATTA eT Al suggesting that loss-of-function of PRRT2 might cause PKD. This hypothesis is supported by the observation that Prrt2 knockout mice show PKD-like phenotypes, 8 although the possibility remains that the truncated mutants might be slightly expressed and cause gain-of-abnormal-function.…”
Section: Introductionmentioning
confidence: 99%